2007
DOI: 10.1007/s11064-007-9533-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dopaminergic Neuron Sensitivity to 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine (MPTP) in Transgenic Mice Expressing Mutant A53T α-Synuclein

Abstract: Familial Parkinson's disease (PD) has been linked to point mutations and duplication of the alpha-synuclein gene and mutant alpha-synuclein expression increases the vulnerability of neurons to exogenous insults. In this study, we analyzed the levels of dopamine and its metabolites in the olfactory bulb (OB), and nigrostriatal regions of transgenic mice expressing human, mutant A53T alpha-synuclein (alpha-syn tg) and their non-transgenic (ntg) littermates using a sub-toxic, moderate dose of MPTP to determine if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…Data expressed as means ± SEM. Asterisk denotes statistical significance (*p<0.05) this area is vulnerable to complex I inhibition (Yu et al 2008). Our study demonstrated increased αSN immunoreactivity in the frontal cortex from rotenone-treated transgenic hA53T αSN mice.…”
Section: Discussionmentioning
confidence: 99%
“…Data expressed as means ± SEM. Asterisk denotes statistical significance (*p<0.05) this area is vulnerable to complex I inhibition (Yu et al 2008). Our study demonstrated increased αSN immunoreactivity in the frontal cortex from rotenone-treated transgenic hA53T αSN mice.…”
Section: Discussionmentioning
confidence: 99%
“…6-Hydroxydopamine toxicity seems to be influenced by alpha-synuclein, since alpha-synuclein-deleted mice are more resistant against 6-hydroxydopamine than their wild type (Alvarez-Fischer et al 2008). Transgenic mice expressing human mutant A53T alpha-synuclein sensitizes dopaminergic neurons to neurotoxic insults and is associated with greater oxidative stress (Yu et al 2008). Early microglial activation with concomitant increase in proinflammatory molecules in mice that over-express wildtype SYN was observed (Su et al 2008).…”
Section: Alpha-synuclein and Parkinson's Diseasementioning
confidence: 97%
“…With respect to the high tolerance of LUHMES towards overexpression of wildtype ASYN, it needs to be discussed that ASYN indeed is not necessarily a cytotoxic protein. Transgenic mice, overexpressing ASYN or its mutant forms (e.g., A30P, A53T), usually do not show neurodegeneration, but some reports indicate an elevated susceptibility following exposure to neurotoxic conditions such as MPTP treatment (Dong et al, 2002;Nieto et al, 2006;Yu et al, 2008). However, others could not detect different susceptibilities between wildtype and ASYN overexpressing mice (Rathke-Hartlieb et al, 2001).…”
Section: Inhibition Of Mitochondrial Movement In Neurites As Early Efmentioning
confidence: 99%